Fusion Splicing for a Large Mode Area Photonic Crystal Fiber with Conventional Single Mode Fiber - Ismail, Shaymaa N.; Taher, Hanan J.; Al-Janabi, Abdul Hadi (Iraqi Journal of Laser, 2019)
In this paper the experimentally obtained conditions for the fusion splicing with photonic crystal fibers (PCF) having large mode areas were reported. The physical mechanism of the splice loss and the microhole collapse property of photonic crystal fiber (PCF) were studied. By controlling the arc-power and the arc-time of a conventional electric arc fusion splicer (FSM-60S), the minimum loss of splicing for fusion two conventional single mode fibers (SMF-28) was (0.00dB), which has similar mode field diameter. For splicing PCF (LMA-10) with a conventional single mode fiber (SMF-28), the loss was increased due to the mode field mismatch.